2014
DOI: 10.1016/j.phrp.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factors of Staphylococcus aureus Isolates in an Iranian Referral Children's Hospital

Abstract: ObjectivesThe clinical importance of Staphylococcus aureus (S. aureus) is attributed to notable virulence factors, surface proteins, toxins, and enzymes as well as the rapid development of drug resistance. The aim of this study was to compare the occurrence of virulence factors produced by S. aureus strains isolated from children in an Iranian referral children's hospital.MethodsThe presence of genes encoding for the enterotoxins A (sea), B (seb), C (sec), D (sed), TSST-1 (tsst), exfoliative toxin A (eta), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
24
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 18 publications
8
24
3
Order By: Relevance
“…However, high detection frequencies of eta (11.3%) and etb (9%) were reported in Sabouni study [29] and almost the same incidence was reported in other studies [6,30,31]. This may be sensible because none of the MRSA strains in the current survey was isolated from children with skin diseases including staphylococcal scalded skin syndrome (SSSS), impetigo, or blisters.…”
Section: Discussionsupporting
confidence: 51%
“…However, high detection frequencies of eta (11.3%) and etb (9%) were reported in Sabouni study [29] and almost the same incidence was reported in other studies [6,30,31]. This may be sensible because none of the MRSA strains in the current survey was isolated from children with skin diseases including staphylococcal scalded skin syndrome (SSSS), impetigo, or blisters.…”
Section: Discussionsupporting
confidence: 51%
“…There are wide differences in the reported geographical distribution of MRSA, from 2.9% to 8.7 % in Turkish nasal carriers and respiratory tracts of ill persons (3, 23), up to 38.7% in Colombia (16), 39.6% in India (24), 41-48% in Iran (25,26) and 44% in Nigeria from animal samples (27). The methicillin resistance rate observed in this study was 12%, with 7.7% from outpatients and 16.2% from inpatients.…”
Section: Resultsmentioning
confidence: 99%
“…The virulence factors produced by different strains are different. For example, Gram-negative Pseudomonas aeruginosa produces virulence factors, such as pyocyanin, elastase, lectin, and exotoxin A [47,48], and Gram-positive Staphylococcus aureus produces virulence factors such as fibronectin binding protein, hemolysin, protein A, lipase, and enterotoxin [49,50]. Studies have shown that the production of these virulence factors is regulated by the bacterial QS signaling systems [51,52].…”
Section: Biofilm Formation and Virulence Factorsmentioning
confidence: 99%